The last christology of the West : adoptionism in Spain and Gaul, 785-820 - Cavadini, John C. (Middle Ages series., 1993)
Describes a controversial notion that Jesus was adopted by God at the time of his baptism, which rose in Spain during the Moorish occupation. Focuses on the writings of the main players: Migetius, Beatus, Felix, and Alcuin. Most of the quotations are given only in English; others only in Latin. Annotation c. Book News, Inc., Portland, OR (booknews.com).